Quality of service guarantees based on admission control for IEEE 802.11 wireless ad hoc networks (2015)
Ad hoc networks are temporary associations of wireless nodes that can operate without a central controller. They are characterized by their flexibility and low cost since they do not depend on an infrastructure previously built. Moreover, the only requirement for a node to join an ad hoc network is to have an IEEE 802.11-enabled network interface card. Nonetheless, the operation of an ad hoc network is really challenging, particularly when nodes are transmitting real-time flows. A receiver can be affected by unexpected interference given that nodes can move and, additionally, because all nodes operate, at the same frequency band. In such varying conditions, it is difficult to guarantee the stringent QoS requirements demanded by real-time traffic. Admission control is a technique that addresses the problem of QoS provisioning by restricting the amount of network traffic. The objective of admission control schemes is to estimate the resource availability in order to determine whether or not they are sufficient to guarantee the demands of an incoming flow as well as those of ongoing flows. This thesis studies admission control for ad hoc networks. A comprehensive literature review is presented, which introduces a new categorization of admission control schemes based on the level of node mobility supported. In ad hoc networks, admission control schemes have the responsibility of maintaining the QoS guarantees of admitted flows when nodes can move, and the review highlights the most remarkable features of admission control schemes for networks with low and high mobility. Moreover, the research reported in this thesis demonstrates that measurement-based envelopes can be used in admission control for multihop ad hoc networks. Specifically, it is shown that the envelope of the arriving traffic can estimate the demands of an incoming flow, while the service envelope is useful to infer unused resources along a multihop path. A distributed envelope-based admission control scheme is proposed, which measures the envelopes in trains of probing packets to evaluate the conditions of a previously discovered route. The envelope-based scheme can be easily implemented since it is decoupled from the routing protocol. Furthermore, it does not consume memory and processing resources at intermediate nodes given that the admission process is exclusively controlled by source and destination nodes. Finally, the impact of the routing protocol selection on the operation of the envelope-based scheme is evaluated. It is shown that the envelope-based scheme achieves its best performance when used jointly with the AODV protocol